Diffusion and Adoption of Livestock Deworming Technology in Different Agro-climatic Regions of India (Indian Journal of Extension Education, 2015)
Livestock technologies are generated in various research institutions with the notion to explore the possibilities of uplifting the livelihoods of farming communities. It is generally perceived that the extent of absorption of these technologies in field conditions has always been a researchable issue in India. In this situation, an effort was made to study the diffusion and adoption status of deworming technology in different agro-climatic zones of India using primary and secondary data collected from various accessible resources. Group discussion and personal communication with veterinary officers and other experts was also conducted to gain insight and evolve action plans for effective adoption and diffusion of deworming. The study concluded that there was lack of awareness and poor adoption of deworming due to various constraints faced by farmers in deworming. The study suggests that there is a better scope for improving the diffusion and adoption of livestock deworming by means of addressing these constraints and creating favourability of livestock farmers towards livestock deworming technology.